Characterization of microplastic pollution in coastal sediments of Vietnam - Le, Xuan Thanh Thao; Duc Long, Huynh; Luu, Thi Trang; Do, Van Manh (Vietnam Journal of Marine Science and Technology, 2026)
Microplastics have increasingly been recognized as an emerging pollutant and have attracted considerable global scientific attention due to their potential impacts on ecosystems and human health. However, information on microplastics in Vietnam’s coastal marine sediments remains limited, fragmented, and has not yet been systematically synthesized. This study provides a systematic review of peer-reviewed publications from 2020 to 2024 that investigated microplastics in coastal marine sediments across Vietnam. Reported concentrations ranged from 0 to 29,232 MPs/kg, with mean values ranging from 2.82 to10,830 MPs/kg. Secondary microplastics were the dominant type, primarily occurring as fibers and fragments. A total of 32 polymer types were identified, among which polyamide (PA), polypropylene (PP), polystyrene (PS), and polyethylene (PE) were the most frequently detected. Overall, the reviewed studies indicate that microplastic contamination has been widely reported in Vietnam’s coastal sediments, although comparisons among studies remain limited by differences in sampling and analytical methods. These findings provide a comprehensive overview of the current status of microplastic pollution in Vietnam’s coastal sediments and serve as an important scientific basis for future monitoring, risk assessment, and management strategies.